Reflection of Pak-Afghan Border in Pashto Literature, Its Impacts on Pashto Language and Linguistic Research (Khairulummah, 2023)
Pashto language is spoken in Pakistan and Afghanistan. It enjoys the status of official language in Afghanistan. It has also remained the official language of former Swat state. In Pakistan, after Punjabi, it is the second largest language. Pashto has rich literary tradition of both written literature as well as of folklore. In various literary genres of Pashto, the impact of Pak-Afghan border, has been reflected. Lack of uniformity in linguistic policy regarding Pashto language, in both of the countries, has also affected the development and planning of Pashto language as well as linguistic research. Development of Pashto language has been affected in terms of establishing a standard and literary dialect and a unified orthographic system in both countries. This article attempts to explore various themes of the impacts of Pak-Afghan border as reflected in Pashto literature. It will also find out border impacts on Pashto language planning and linguistic research.
Keywords: Pak-Afghan border, Durand Line, Pashto language, Pashto poetry, Pashto dialects, Border studies.